Silent Threat: Ascending Aortic Dissection Triggering Congestive Heart Failure in A Young Indonesian Woman Suspected of Marfan Syndrome – A Case Report - Shinta Dewi Rasti; Richardus Rukma Juslim; Febryanti Hartono (Cardiovascular and Cardiometabolic Journal (CCJ), 2024)
Highlights: 1. Thoracic Aortic Aneurysm is not frequently discussed. However, this study analyzed it and pointed out how life-threatening a disease with silent nature could be. 2. It shows how screening for patient needed to be conducted thoroughly to ensure there is no potential threat left undiagnosed. - Background: A considerable number of thoracic aortic aneurysms (TAAs) remain unidentified or misdiagnosed owing to the silent nature of the disease and the lack of a screening program. The diagnostic process is frequently intricate, leading to potentially catastrophic outcomes. Case presentation: A 32-year-old woman presented with shortness of breath and swelling in both legs, resembling symptoms of heart failure. Despite the absence of known cardiovascular risk factors, echocardiography unveiled a critical condition; painless ascending aortic aneurysm with dissection, posing a life-threatening risk. Conclusion: Initially, the patient's susceptibility to the disease was not readily apparent. Interestingly, aortic dissection patients presenting with heart failure symptoms were less inclined to experience chest pain compared to those without such symptoms. This disparity might triple the time required for diagnosis and elevate mortality risk to 33%. Thus, this case report aims to increase awareness in the medical community about rare and subtle cases that might be overlooked or misdiagnosed due to atypical presentations.